Case Report: Primary intravenous synovial sarcoma in the proximal great vein: a case report and literature review - Tang, Wenjian; Wu, Zhen; Huang, Rong; Wei, Jiawang (Frontiers in Oncology, 2025)
Primary intravenous synovial sarcoma (PISS) is an extremely rare disease originating from pluripotent mesenchymal stem cells, and has the potential to develop in nearly any part of the body. This report describes the case of a 54-year-old man who presented with a 20-day history of neck and facial swelling. Imaging findings on contrast-enhanced CT and 18F-FDG PET/CT revealed filling defects with markedly increased FDG uptake with involvement of multiple venous structures, including the superior vena cava, brachiocephalic vein, and left internal jugular vein, and enlarged lymph nodes near the aortic arch. A vascular interventional biopsy confirmed PISS. Here, we discuss the clinical characteristics and imaging findings of PISS and review 14 cases reported in previous studies.